1997
DOI: 10.1002/pro.5560060709
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a stable intermediate on the folding pathway of protein A

Abstract: The B-domain of protein A has one of the simplest protein topologies, a three-helix bundle. Its folding has been studied as a model for elementary steps in the folding of larger proteins. Earlier studies suggested that folding might occur by way of a helical hairpin intermediate. Equilibrium hydrogen exchange measurements indicate that the C-terminal helical hairpin could be a potential folding intermediate. Kinetic refolding experiments were performed using stopped-flow circular dichroism and NMR hydrogen-deu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
136
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(174 citation statements)
references
References 64 publications
37
136
1
Order By: Relevance
“…These evolving ensembles exhibit a folding mechanism where secondary structure formation is coupled with solvent exclusion and core formation. We find that helix III forms early, consistent with experiments (19) and most calculations (12,15,17). The results of Bockzo and Brooks (7) differ from ours on this specific detail.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…These evolving ensembles exhibit a folding mechanism where secondary structure formation is coupled with solvent exclusion and core formation. We find that helix III forms early, consistent with experiments (19) and most calculations (12,15,17). The results of Bockzo and Brooks (7) differ from ours on this specific detail.…”
Section: Resultssupporting
confidence: 81%
“…For our studies, a natural choice is the 10-55 helical fragment B of protein A from Staphylococcus aureus, using the replica exchange molecular dynamics (REMD) algorithm described by Sugita and Okamoto (5). Protein A folds into a simple three-helix bundle (6) whose folding has been widely studied by using minimalist and all-atom simulations (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) as well as experiments (18,19). All of these different studies provided some information about the folding mechanism and the nature of the transition-state ensemble (TSE).…”
mentioning
confidence: 99%
“…Strong protection, > 40%, was observed in experiments and predicted by the simulation for peptides spanning the region from residues 48-159, (βα) 2-5 β 6 . The simulation overestimated the protection at the Nterminus for residues 9-47, α 0 (βα) 1 and near the C-terminus for residues 146-179 (βα) 6 . The most apparent discrepancy exists at the N-terminus where the simulation predicts very strong protection in peptide 1-8 and the HX-MS results show just the absence of protection.…”
Section: Gō-model Simulation Of Sigps Folding Mechanismmentioning
confidence: 89%
“…An extensive mutational analysis of the equilibrium intermediate for αTS 54,55 demonstrated that a tightly-packed Nterminal region, (βα) [1][2][3][4] , is not tightly coupled to a molten globule-like C-terminal region containing (βα) [5][6][7][8] . This differential behavior was attributed to misfolding at the boundaries of the (βα) [1][2][3][4] region that precluded propagation to the C-terminal region in the I1 intermediate. The possibility of misfolding at the periphery of an N-terminal core is supported by the results of another mutational analysis of a pair of long-range H-bonds in the N-terminal region between aspartic acid side chains at the C-termini of two helices and main chain amide hydrogens near the N-termini of their preceding β-strands.…”
Section: Why Are the On-and Off-pathway Intermediates For (βα) 8 Barrmentioning
confidence: 99%
See 1 more Smart Citation